Consumo e influência de exopolissacarideos de Anabaena spiroides (Cyanophyceae) sobre a toxicidade e captura do cobre por Ceriodaphnia cornuta (Cladocera, Daphnidae) - Choueri, Rodrigo Brasil (Universidade Federal de São Carlos, 2004)
Human specie can alter deeply and very fast the enviroment in which it is in. Because of the industrial development, the water, air and soil contamination have become cause of concern, chiefly in big cities with great populations. Among the contaminants figure the heavy metals, which levels at aquatic and terrestrial ecossistems are growin up every year. These elements are able to bioaccumulate in the organisms and biomagnified on the food webs. The bioavailability of metals can be influencied by several factors like the complexation with dissolved organic matter, e.g. algal exudates, that generally decreases the toxicity of this elements. The scope of this work was evaluate the potencial use of exopolysccharides of Anabaena spiroides (Cyanophyceae) as food source of Ceriodaphnia cornuta (Cladocera, Daphnidae), and to establish the influence of this organic matter on copper toxicity and uptake to this cladoceran. Initially, it was estabilished the C. cornuta length-weigth relation. After this, it was investigated ingestion of exopolysccharide and its influence in life history parameters of C. cornuta. Results showed that A. spiroides exopolysccharide is able to sustain a population of this zooplanktonic specie. Individuals fed with this compound exhibited rate of population growth very significant to this specie (r = 0,263). The copper acute toxicity and uptake by C. cornuta assay revealed that addition of 30mg L-1 of A. spiroides exopolysccharide increased about 4 times copper EC/50 (calculated by Trimmed Spearman-Karber method) to C. Cornuta (from 8,11x10-8M ±9,80x10-9M without exopolysccharide to 3,25x10-7M ±5,30x10-8M with addition of exopolysccharide). Copper concentration in the organisms after 24 hours exposure to several metal concentration was determined by DPASV using a polarograph and showed little variation among concentrations and treatments with and without exopolysccharide. It suggests that organisms of this study were able to regulate copper body contents.
Keywords: Limnologia; Ecotoxicologia; Cobre; Anabaena spiroides; Ceriodaphnia cornuta; CIENCIAS BIOLOGICAS::ECOLOGIA